Characterization of the elemental and particle load of patient exhaled breath condensate and comparison with pulmonary lavages. (1st January 2023) - Marie-Desvergne, Caroline; Dubosson, Muriel; Leclerc, Lara; Campo, Catherine; Bitounis, Dimitrios; Forest, Valérie; Pourchez, Jérémie; Cottier, Michèle; Vergnon, Jean-Michel; Tarantini, Adeline; Chamel-Mossuz, Véronique
Abstract: In the field of biomonitoring, exhaled breath condensate (EBC) is described as a potentially useful matrix for assessing inhalation exposure biomarkers in a non-invasive way. However, it is still unclear to what extent EBC is representative of the deep lung. To address this knowledge gap, EBC, bronchial washes (BWs), and bronchoalveolar lavages (BALs) were collected from 82 patients suffering from interstitial lung diseases (ILDs). The particulate contents and elemental composition of EBC, BW, and BAL were then compared in the same patients. The size distribution of particles in EBC was assessed with dynamic light scattering while inductively coupled plasma mass spectrometry was used to quantify its elemental composition. In addition, transmission electron microscopy coupled with energy dispersive x-ray spectrometry were used to further characterize samples of interest. EBC was found to be representative of both the sub-micron and nano-sized particle fractions of BAL and BW, with lower overall levels of elements in EBC than in BW and BAL. Silicon (Si) was the main component for all respiratory matrices with median levels of 2525 µ g l −1, 5643 µ g l −1 and 5169 µ g l −1 in the nano/ion fractions of EBC, BAL and BW, respectively. Moreover, Si levels in EBC from patients in this study were elevated compared to the levels reported in the literature for healthy subjects. Interestingly, Si levels in the EBC of ILD patients were inversely related to those in BAL and BW. In conclusion, the particulate content of EBC is associated with the lung particle burden and potentially correlates with pathologies, rendering it a relevant biomonitoring technique for the occupational and clinical fields.